The Impact of El Nino on Inflation in Regional Indonesia: Spatial Panel Approach - Fahmi Salam Ahmad; Hermanto Siregar; Syamsul Hidayat Pasaribu (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2019)
The study about the relationship between climate and economy is essential because it’s understanding is the key to formulate the effective economic policy. El Nino is one of the climate phenomena's that directly impact Indonesia, so it is necessary to analyze its effect on the macroeconomic condition such as inflation. This study aims to analyze the impact of El Nino as an external factor and the impact of another relevant economic factor on the macroeconomic condition such as inflation at the regional level (province) in Indonesia. The method used is a spatial panel method to capture the effect of inter-regional spatial interactions. The results show that El Nino has a positive effect on inflation in the southern Indonesian provinces that are affected by El Nino, but no effect in northern Indonesia. The other significant determinants of regional inflation are minimum wage, local revenue, local government spending, and infrastructure. There is significant spatial dependence on regional inflation in Indonesia, indicating that the inflations of its neighboring provinces influence the inflation of a province.